2010
DOI: 10.1590/s0100-736x2010001000014
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of American bullfrog tadpoles to stressor conditions of capture and hypoxia

Abstract: RESUMO.-[Resposta fisiológica de girinos de rã-touro americana submetidos aos mecanismos estressores de captura e hipóxia.] A rã-touro americana (Rana catesbeiana) recentemente denominada Lithobates catesbeianus é criada com propósito comercial em várias regiões do Brasil. Situações estressantes tais como problemas de manejo, criação inadequada e alterações ambientais com consequente redução da imunidade são comuns em produções intensivas. A avaliação destas situações de estresse permitenos detectar estes prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
3
6
0
2
Order By: Relevance
“…The red series haematological parameters for animals exposed to the stressor mechanisms are presented in Ta (Coppo et al2005) and values about Ht 22,5±5%; Hb 4,7±0,9g/100mL (Cathers et al 1997) . There were not significant differences between the treatments in the different collection days corroborating the reports from another study (Rocha et al 2010) on the same species of tadpoles.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The red series haematological parameters for animals exposed to the stressor mechanisms are presented in Ta (Coppo et al2005) and values about Ht 22,5±5%; Hb 4,7±0,9g/100mL (Cathers et al 1997) . There were not significant differences between the treatments in the different collection days corroborating the reports from another study (Rocha et al 2010) on the same species of tadpoles.…”
Section: Resultssupporting
confidence: 90%
“…However, these authors reported qualitative uncertainties regarding the analysed material, referring to it as "cortisol like". Studies with tadpoles of the same species and in the same developmental phase, found mean plasma cortisol values ranging from 2.14 to 5.0ng/mL after exposing the animals to the stressors capture and hypoxia (Rocha et al 2010). The Kruskal-Wallis test indicated that tadpole density had no effect on cortisol concentration.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Native to the eastern United States and Canada (GIOVANELLI et al, 2008;BOTH et al, 2011), L. catesbeianus was introduced in Brazil in the 1930s, in association with aquaculture (GIOVANELLI et al, 2008;ROCHA et al, 2010). L. catesbeianus was included in this study because of its economical importance and the variety of hematologic studies of this species available (CATHERS et al, 1997;COPPO et al, 2005;DAVIS, 2009;ROCHA et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…L. catesbeianus was included in this study because of its economical importance and the variety of hematologic studies of this species available (CATHERS et al, 1997;COPPO et al, 2005;DAVIS, 2009;ROCHA et al, 2010).…”
Section: Discussionmentioning
confidence: 99%